IMPACT OF COMMERCIAL BANK’S CREDIT ON MANUFACTURING SECTOR OUTPUT IN NIGERIA - Ibrahim Musa; El-Yaqub Ahmad. B.; Sule Magaji (Journal of Applied Economics in Developing Countries, 2024)
This study examines the impact of commercial banks' credit (CBC) on manufacturing sector output (MSO) in Nigeria from 1992 to 2021 using Ex-Post Factor Research Design Approach. The study’s findings indicate that commercial banks credit (CBC) has a beneficial and substantial impact on manufacturing sector output (MSO). The long-term value of CBC has a positive and substantial impact on MSO. A 1% rise in Credit to Small and Medium Businesses (CSM) led to a 0.1866% increase in MSO. Conversely, a unit increase in deposit interest rate (DINR) resulted in a 0.0081% fall in MSO. In the long run, a unit increase in Government Capital Expenditure (GOV) caused a 0.1482% increase in MSO. Therefore, the study recommends that using its monetary policies, federal government can make an efficient policy that allows the manufacturing sector and small and medium enterprises to access bank credit at low interest rates.